Reintroducing B. infantis to the cesarean‐born neonate: an ecologically sound alternative to "vaginal seeding". Issue 6 (18th February 2020) - Duar, Rebbeca M; Kyle, David; Tribe, Rachel M
ABSTRACT: There is a burgeoning literature highlighting differences in health outcomes between babies born vaginally and by caesarean section (c-section) This has led to the suggestion that infants born by c-section may benefit from vaginal swabbing/seeding. Here, we discuss from an ecological perspective that it is gut-adapted, not vagina-adapted microbes that are likely to take up residence in the gut and have the most beneficial impact on the developing neonate. Further, we caution the practice of 'vaginal seeding' may be potentially unsafe and also give parents and health professionals a false sense of action in restoring the infant gut microbiome following c-section. Instead, we argue that restoring B. longum subsp. infantis, which has evolved to colonize the infant gut, is a safe and ecologically-sound approach to restoring the gut microbiome of infants born by c-section. Abstract : Restoring the gut microbiome of infants delivered by cesarean section with B. infantis .